Development of Serial Image Media In The Form of Pop-Up E-Books to Improve The Reading Skills of Class I Students in The Independent Curriculum - Fitria Sari; Amar Salahuddin; Eza Susanti (The Future of Education Journal, 2024)
Media is a vehicle for transmitting learning information or transmitting messages. The word media comes from Latin, namely medius, which means middle, intermediary, or introduction. Media means an intermediary or messenger from the sender to the message recipient. The broad meaning is activities that can create conditions that enable students to acquire knowledge and attitudes. The aim of this research is to see whether the development of serial image media in the form of pop-up e-books can improve the reading skills of class I students in the independent curriculum. The type of research used in this research is research and development. Research and development (R&D) is a type of research that focuses on products. The results of the research show that serial image media in the form of pop-up e-books is said to be very valid, where the average for validator material is 83% while for media experts it is 85%. Based on the results of the research and discussions that have been carried out, it can be concluded as follows. Pop-up book media that is suitable for reading for grade I elementary school students is a pop-up book that pays attention to aspects of the material that supports the content of the learning material and is in accordance with the characteristics of elementary school students.